Killing Under Masks – Death by Rusalia (Vasilichari) Groups in Ottoman Macedonia in 19th Century - Koviloski, Slavcho (Poznańskie Studia Slawistyczne, 2023)
In this text, we refer to the killing by the rusalia groups (also known as babar or jamalar groups) whose members were wearing masks during the so-called unbaptized days (from January 7 to 19). In these centuries-old rites, old Slavic pre-Christian customs are mixed with Christian celebrations. Our interest relates to a pagan custom performed in the time of Ottoman Macedonia in the 19th century. Back then, the meeting of two such groups ended with bloodshed and the death of individuals caused by knives or sticks. The deceased were buried in the place where they were killed, thus there are rusalia, babar or jamalar graves in several locations.